Morphologic variability of the Acer campestre L. populations in Bosnia and Herzegovina - Stjepan Kvesić (Pensoft Publishers, 2021)
Morphologic variability from 25 populations of Acer campestre L. in Bosnia and Herzegovina was analyzed. Morphometric structure of variability and between-population variability was performed based on 10 fruit-parameter characteristics and 19 leaf-parameter characteristics using multivariate statistical analysis. Results confirmed the separation of three submediterranean populations as a group in relation to other tested populations, from which the Banja Luka population is different. Measured leaf parameters were confirmed as a predominant carrier of the morphologic separation between populations. In other Acer species populations within A. monspessulanum and A. intermedium species are separated mainly by fruit and much less by leaf parameters. The southernmost submediterranean populations from Trebinje, Ljubuški, and Mostar regions have smaller leaf areas, which consequently places them within the same morphologic group; their variability is in tight connection with eco-geo-graphical factors, where the ecological distance is a much better predictor of morphological variability compared to geographical distance. The air temperature had the biggest influence on morphological variability regarding the highest in-between correlation. Achieved results may serve for the continuation of the research in other areas of Acer campestre to determine the interactive effect of ecological, geographical, climatic, and migrational factors on their morphologic population plasticity.